Analysis and proposition of limiting current density measurement protocol. (1st July 2022) - Wang, Shixue; Liang, Ya'nan; Li, Dewei; Zhang, Zengming; Zhang, Jianbo
Abstract: Limiting current density at different temperatures, backpressures, and balance gases can be used to separate molecular diffusion resistance, Knudsen diffusion resistance and local transport resistance of membrane electrode assembly (MEA). However, the measurement of limiting current density has no unified protocol. The diverse choices in the literature, either in the control of current or voltage or in the atmosphere like relative humidity and O2 concentrations, make it difficult to compare the results and identify the true bottleneck hindering the mass transport. In this work, the current-voltage curves obtained by current scanning/stepping and voltage scanning/stepping methods under dilute O2 of different concentrations and a wide range of relative humidity were measured and analyzed systematically. It is found that the voltage stepping method is superior to the other three ways of control for the reliable determination of the limiting current density. Aided with simultaneous electrochemical impedance spectroscopy measurement, the limiting current density can be determined with pinpoint accuracy. When the limiting current density is just used to qualitatively evaluate different MEA, the voltage scanning method can be used instead for its high time efficiency. The selection of the atmosphere also plays an important role in suppressing the distortion from excessive water and reducing the spurious contribution from proton conduction resistance. It is found that O2 concentrations at 0.5 vol% and relative humidity at 90% can give the best estimation of O2 transport resistance in membrane electrode assembly. Highlights: Four types of LCD measurement methods were analyzed systematically. LCD measurement atmosphere has a great effect on O2 transport resistances. Aided with EIS measurement, the LCD can be determined with pinpoint accuracy. The pinpoint accuracy LCD measurement protocol was proposed.